Innovating workplace learning: Training methodology analysis based on content, instructional design, programmed learning, and recommendation framework - Kim, Sehoon (Frontiers in Psychology, 2022)
The quality of sales processes is crucial in automotive and directly related to the firm’s competitive advantage and financial success. Sales training is the most prevalent intervention to guarantee quality and productivity. Extant literature has attempted to measure training effectiveness adequately, and the Context, Input, Process, and Product evaluation (CIPP) model has been a popular approach. This study endeavored to advance current literature and suggest a novel effectiveness framework, Content, Instructional design, Programmed learning, and Recommendation (CIP-R). The framework was applied to examine three different methodologies—traditional, pure digital, and hybrid training—collecting 583 instances from the automotive sales training conducted from 2019 to 2020 in South Korea. The findings advocate the importance of human elements, the role of efficacy, and self-determination in generating learning transferability, leading to performance in the digital age.